Preparing students as future professionals for creative economy - M. I. Kotenko; P. V. Pavlovskiy (Вестник университета)
Creative economies contribution to the total gross domestic product of countries has been analyzed. Issues have been identified in students preparation in higher education institutions in terms of creative competencies formation, considering existing market features and challenges. Creative economy market analysis has been carried out, as a result of which a shortage of qualified specialists has been found. The relevance of the issue of forming creative competencies among future specialists has been substantiated, considering current requirements and recommendations of industry enterprises representatives. A solution to the issue of personnel shortage has been proposed based on implementation of new and processing existing educational approaches, considering the digital transformation trends in the Russia. The digital transformation impact on a future specialist’s competencies, considering the industry demands, has been established. The necessity of changing the traditional approach to organizing educational process in the context of the post-industrial information society is substantiated. A new approach to the development of creative abilities and the effective use of the creative potential of students of educational institutions of higher education has been proposed. The key competencies of management personnel have been systematized. Based on an expert assessment, the key creative skills of a manager in the era of digital transformation have been identified. Priority tasks have been identified, the solution of which will contribute to forming an effective system of creative training of managerial personnel.